Occurrence of the alcoholic tolerance phenomenon and their relationships with daily frequency of ethanol doses and with the presence of an withdrawal interval, in an experimental model of alcoholism in rats - J. O. Cardeal; E. A. Cavalheiro (Arquivos de Neuro-Psiquiatria)
In this paper we present the effects of the number of daily toxic doses of alcohol and of the duration of withdrawal period on alcohol tolerance in rats submitted to cycles of 21 doses each. It was observed that alcohol tolerance was increased in animals which received less number of alcohol doses by day and that some degree of tolerance can be detected even after a withdrawal interval of 15 days.